Evaluation of Feasibility of 2 Novel Heart Failure Monitoring Instruments to Facilitate Patient Recognition of Symptoms. Issue 1 (January 2016) - Wakefield, Bonnie; Groves, Patricia; Drwal, Kariann; Scherubel, Melody; Kaboli, Peter
Abstract : Purpose: To maintain clinical stability, patients with heart failure (HF) must recognize often subtle but clinically significant symptoms that can precede decompensation. The primary objective of this study was to evaluate the feasibility of 2 patient self-monitoring instruments designed to facilitate both HF symptom recognition and reporting of these symptoms to providers. Secondary goals included assessment of actions taken by patients when their symptoms indicated potential HF decompensation, changes in self-care management, and patients' perceptions of the usefulness of the instruments in symptom monitoring. Methods: A pretest-posttest longitudinal design was used for the study. Data were collected at a Midwestern Veterans Affairs Medical Center. Participants used 2 paper-based graphs to monitor weight and dyspnea daily for 3 months. The participants were interviewed at baseline about self-care activities and, at study completion, about perceptions and use of the graphs. The Self-Care of HF Index was administered at baseline and completion to assess for changes in self-care. Results: Thirty-one participants completed the study. Most participants (97%) were men, white (94%) with a mean age of 68 years (range, 45–81). At baseline, systolic ejection fraction mean was 37.6% with a range of 10% to 65%. Most participants demonstrated a willingness to use the instruments for monitoring (range of adherence, 63–84 d [75%–100% of the study period], with a mean [SD] use rate of 79.9 [6.4] d). The participants with potential exacerbations rarely took action based on the data. The use of the instruments had no significant effect on self-management behaviors during the 3-month period. The participants reported that they found the instruments helpful and would recommend them to other patients with HF. Conclusions: New strategies and instruments are needed to promote a patient-clinician partnership and actively engage patients in symptom monitoring and recognition. Easy-to-use and practical instruments for patients to monitor symptoms may lead to appropriate and accurate reporting as well as improved symptom management. Although the instruments used in this study resulted in symptom monitoring, appropriate action was not undertaken as a result of such monitoring.